Bathyraja (Arctoraja) sexoculata sp. nov., a new softnose skate (Rajiformes: Arhynchobatidae) from Simushir Island, Kuril Islands (western North Pacific), with special reference to geographic variations in Bathyraja (Arctoraja) smirnovi - Misawa, Ryo; Orlov, Alexei M.; Orlova, Svetlana Y.; Gordeev, Ilya I.; Ishihara, Hajime; Hamatsu, Tomonori; Ueda, Yuji; Fujiwara, Kunihiro; Endo, Hiromitsu; Kai, Yoshiaki (Zootaxa, 2020)
A new species of softnose skate (Arhynchobatidae), Bathyraja sexoculata Misawa, Orlov, Orlova, Gordeev and Ishihara is described on the basis of five specimens collected from off the east coast of Simushir Island, Kuril Islands, located in the western North Pacific. The specimens conformed to the genus Bathyraja by having the anteriormost pectoral-fin skeleton almost reaching the snout tip, and a slender unsegmented rostral cartilage. Within Bathyraja, the new species belongs to the subgenus Arctoraja (currently with four valid species) due to the relatively short tail (79–86% of disc width), high count of predorsal caudal vertebrae (more than 86), and large strong nuchal and scapular thorns. It is most similar to Bathyraja (Arctoraja) smirnovi, distributed in the Seas of Japan and Okhotsk, in having tail thorns not extending to the nuchal area, median thorns discontinuous from the nape to the tail, and no mid-dorsal thorns. However, B. sexoculata can be distinguished from B. smirnovi by the following characters: three pairs of white blotches on the dorsal disc surface (vs. blotches absent, or a pair of white or dark blotches in B. smirnovi), dark blotch around cloaca, dark bands along mid ventral line of tail (vs. dark blotch and band usually absent ventral disc surface in B. smirnovi), 86–93 predorsal caudal vertebrae (vs. 80–87 in B. smirnovi), and a unique mitochondrial DNA cytochrome c oxidase subunit I sequence. Proportional measurements, including disc width, disc length, head length, preoral length, prenarial length, internarial distance, eye diameter, and tail length, also differ between the two species. For the referential purpose, geographical variations of B. smirnovi distributed in the Seas of Japan and Okhotsk are analyzed and clarified based on morphological and genetic data. Significant morphological and genetic differences were found between local populations in the Seas of Japan and Okhotsk.